Society 5.0: First International Conference, Society 5.0 2021, Virtual Event, June 22-24, 2021, Revised Selected Papers - Gerber, Aurona; Hinkelmann, Knut (Communications in Computer and Information Science, 2021)
This book constitutes revised and selected papers from the First International Conference on Society 5.0, Society 5.0 2021, held virtually in June 2021. The 12 full papers and 3 short papers presented in this volume were thoroughly reviewed and selected from the 54 qualified submissions. The papers discuss topics on application of the fourth industrial revolution innovations (e.g. Internet of Things, Big Data, Artificial intelligence, and the sharing economy) in healthcare, mobility, infrastructure, politics, government, economy and industry.